Illocutionary Act of Modal Auxiliary Can In HBO Series Game of Thrones - Zahra, Dewi; Parthama, I Gusti Ngurah (Humanis; Vol 22 No 3 (2018), 2018)
This study is entitled Illocutionary Acts of Modal Auxiliary Can in HBO Series Game of Thrones. This study is aimed at analyzing and classifying the types of illocutionary act and its force through the modal auxiliary can in Game of Throne Series. Besides, this study also tries to explain the context of situation that supports the illocutionary act in Game of Throne Series.The library research was used to collect the data which carried modal auxiliary can from the TV series and descriptive qualitative method was used to analyze the data. The Taxonomy of Illocutionary Acts proposed by Searle (1979) about classification of illocutionary act was used to classify the data and classify them to the types of the acts with the purpose to know the force of the illocutionary acts. Theory of context of situation proposed by Halliday was applied to show how the context of situation (field of discourse, tenor of discourse, and mode of discourse) support the illocutionary  acts found in Game of Throne Series.The result of the analysis showed that there were five types of illocutionary acts found in Game of Throne Series, the y are ; assertive, directive, commissive, expressive, and declarative. The forces  found in the analysis are ; suggesting, telling, stating, asking, entreating, promising, attitudes, refusing, intending, complaining, defying, and declaring.